Paradise lane - Taylor, William, 1938- (New York : Scholastic, 1987)
When fifteen-year-old Rosie Perkins, an outcast at school, saves the life of a baby opossum, she finds an unlikely friend and ally in Michael Geraghty, a classmate who is her complete opposite.
Keywords: Opossums -- Fiction; Friendship -- Fiction; Family problems -- Fiction; New Zealand -- Fiction